Panacea or Corporate Tool?: Debunking the Supreme Court's Preference for Binding Arbitration - Jean R. Sternlight (Washington University Law Quarterly, 1996)
This Article does not advocate reviving the old hostility toward binding arbitration. Rather, the Court should once again apply the Federal Arbitration Act as it was intended to be applied: to accept binding arbitration where it is fair and has been accepted by the parties, and to reject binding arbitration where it has been foisted unfairly upon a weaker party. If the Court fails to change its course, Congress should step in to ensure that binding arbitration is used to further rather than defeat justice.
Keywords: Arbitration clauses (Contracts); Consumer protection; Covenants; Exclusive & amp; concurrent legislative powers